Embodying the suffering of hunger through the art of ceramics: “The Loaf” as a visual symbol (Al-Academy, 2025)
This research paper addresses the subject of representing hunger through the embodiment of the symbolism of the "loaf" using installation art in space. The study aims to explore the human dimensions associated with hunger and satiety, using the loaf as a symbol of life and abundance in a contemporary context. The importance of the research lies in highlighting the role of visual arts in raising awareness of hunger as a humanitarian issue, especially in light of global crises such as the COVID-19 pandemic and wars that have affected food security. The main question posed in the research is how to use ceramic art and installation art in space as a means of expressing feelings of deprivation and hunger. The study relied on the historical approach, tracing the appearance of the loaf in contemporary artworks, in addition to the artistic analysis of the works of artists who used the loaf as a symbol to express different meanings. A purposive sample of six contemporary artists who worked on integrating the loaf into their artworks was selected, and their techniques and interpretations of the symbolism related to hunger were analyzed. The study also addressed contemporary treatments that use installation art in space to represent hunger. The results showed that installation art in space can be powerful tools for expressing social and humanitarian issues such as hunger. It was found that contemporary artists use these media to evoke feelings of interaction with the audience and convey strong messages about poverty and hunger. The study recommended expanding the use of these artworks in exhibitions and museums to increase public awareness and stimulate dialogue about global issues related to hunger.